Ukranian Russian Crisis between Ambitions and Ukrain tendency towrd Europe - الزهيزي ستار شدهان (lark, 2019)
The outbreak of Russian and Ukrainian crisis due to many results such as the problem of energy and Ukrain policy in Guam organization ,Ukrain position tword the black see’s fleet and its support to Gorgian in announcing the war against the south region of Ossetia.This crisis has a political consequences such as the increas of divisions in Ukrain, destroying the Ukrain economy, Ukrain social disengagement instead of the crisis reflection on political, economic and security positions .